How to conduct paired-t-test SPSS: comprehension in adsorption with bibliometric - Asep Bayu Dani Nandiyanto; Siti Nur Hofifah (International Journal of Evaluation and Research in Education (IJERE), 2024)
The purpose of this study was to provide an example of how to calculate, measure, and interpret a paired t-test analysis using Statistical Package for the Social Sciences (SPSS). This study explained a step-by-step process to understand how t-test analysis can be used. To support this study, bibliometric research was added for showing the research trend in the use of t-test in a wide range of applications in the medical and educational fields. The analysis was carried out in two stages, namely prerequisite testing and hypothesis testing. In the prerequisite test, we did the normality (the Shapiro-Wilk) and the homogeneity test (Levene). Both tests were used for understanding what a significant impact happens on student learning outcomes from the statistical data gained during the teaching and learning process. Since this study provided step by step on conducting the t-test using SPSS and also how to interpret the results, this study is applicable for users to use in various research fields.